Analisis Metode Dakwah (Qs. An-Nahl [16]125) Dalam Perspektif Filsafat Manajemen Dakwah - al-Manduri, rohman (FDIK IAIN Padangsidimpuan, 2024)
The development of the digital era demands a more systematic and structured approach to da'wah management. This study aims to analyze the integration of da'wah management philosophy through the study of QS. An-Nahl [16]: 125. The research uses a qualitative method with a philosophical-normative approach through analysis of tafsir and management literature. The results showed that da'wah leadership requires three main competencies (technical skills, human skills, conceptual skills) integrated with Qur'anic values. Its implementation is realized through the POAC function (planning, organizing, actuating, controlling) and three da'wah methods: bil-hikmah, mau'idzah hasanah, and mujadalah. The study concluded that the effectiveness of contemporary da'wah requires a synthesis between Islamic values and modern management principles through an adaptive philosophical approach.